2020
DOI: 10.3892/br.2020.1295
|View full text |Cite
|
Sign up to set email alerts
|

Cyst of the Canal of Nuck in adult females: A case report and systematic review

Abstract: Defects in the Canal of Nuck are rare abnormalities of the female genitalia, which are typically detected and repaired in young age. In the present report, a case of a Nuck cyst in a 40-year old female patient is described. Additionally, the current literature concerning cases of women with hydrocele of Nuck canal was systematically reviewed. A total of 16 case reports of 16 patients with Nuck hydrocele (mean age of 35.18 years), have been reported to date. A right inguinal mass was noted in 13 patients (81.3%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(46 citation statements)
references
References 32 publications
0
44
0
2
Order By: Relevance
“…Imaging, especially ultrasound (US), is helpful for timely diagnosis; Doppler ultrasound can confirm intestinal obstruction and ischemic necrosis [ 5 ]. It has been reported that CT scan or magnetic resonance imaging can more effectively observe the anatomy around the cyst and determine whether the cyst communicated with the abdominal cavity [ 1 ]. Even so, in some cases, the final diagnosis depends on the intraoperative findings [ 4 , 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Imaging, especially ultrasound (US), is helpful for timely diagnosis; Doppler ultrasound can confirm intestinal obstruction and ischemic necrosis [ 5 ]. It has been reported that CT scan or magnetic resonance imaging can more effectively observe the anatomy around the cyst and determine whether the cyst communicated with the abdominal cavity [ 1 ]. Even so, in some cases, the final diagnosis depends on the intraoperative findings [ 4 , 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hydrocele of canal of Nuck (HCN) is a rare disease in adult women that is difficult to diagnose by preoperative imaging alone, and some patients may have a complicated inguinal hernia [ 1 3 ]. The traditional treatment method is to completely remove the hydrocele through an open anterior approach surgery [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Diagnosis of endometriosis in the NC is even more uncommon in patients with patent NC due to failure of the canal to close within the first year of life in females [ 47 ]. The aforementioned defect can result in hydrocele formation or herniation of intraabdominal surrounding tissues through the canal [ 47 ]. Under certain circumstances, which, however, remain unknown, the NC can be infiltrated by endometrial cells and results in the formation of endometriosis.…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, a CT, MRI, or even a PET-CT supplemented the U/S findings. High-resolution U/S is an inexpensive and reliable modality to set the suspicion of diagnosis of the Nuck endometriosis [ 47 ]. Nonetheless, the final diagnosis is based on the histology and immunochistochemistry.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation